1985
DOI: 10.1002/ar.1092120406
|View full text |Cite
|
Sign up to set email alerts
|

Filipin‐sterol complexes in the plasma membrane of zebrafish spermatozoa

Abstract: The presence and distribution of filipin-sterol complexes in the plasma membrane of zebrafish (Brachydanio rerio) sperm was investigated. The zebrafish sperm plasma membrane, treated with freeze-fracture techniques, is seen to contain a multitude of intramembranous particles that, in a specific region of the posterior part of the sperm head, are organized into unusual particle arrays that appear as simple hexagons or parallelograms. The polyene antibiotic filipin forms complexes with 3-beta-OH sterols to produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…Its presence tends to decrease the viscosity and to restrict the mobility of phospholipids and proteins. The regional differences observed in the distribution of cholesterol in the mosquito sperm membrane probably are due to specific functions played by some membrane domains, as already suggested for vertebrate spermatozoa [21,23,36].…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Its presence tends to decrease the viscosity and to restrict the mobility of phospholipids and proteins. The regional differences observed in the distribution of cholesterol in the mosquito sperm membrane probably are due to specific functions played by some membrane domains, as already suggested for vertebrate spermatozoa [21,23,36].…”
Section: Discussionsupporting
confidence: 59%
“…The establishment of surface domains during differentiation of the spermatid may also involve changes in the distribution of phospholipids and sterols. Previous studies have shown that cholesterol plays an important role in the regulation of membrane permeability, fluidity and enzymatic activity [21,23,36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Binding of filipin to membrane sterols is very specific, requiring a planar steroid nucleus, an unesterified 3-hydroxyl group and an apolar side chain at C-17 (Kinsky, 1970;De Kruijff et al, 1974;Norman et al, 1976;Miller, 1984). The interaction results in the formation of a multimolecular filipin-sterol complex that is relatively insoluble in organic solvents and can be recognized in thin sections and in freeze-fracture replicas (Tillack and Kinsky, 1973;Elias et al, 1978Elias et al, , 1979Kessel et al, 1985).…”
Section: Introductionmentioning
confidence: 99%